Kesehatan Mulut dan Nutrisi Optimal Dalam Membangun Kemandirian Kesehatan Generasi Emas di Sekolah Dasar (SD N Glagahwero 2 Jember) - Candra Dewi, Riskha Dora; Suryono, Suryono; Karimah, Rinda Nurul (Universitas Respati Indonesia, 2024)
Background: Oral health and optimal nutrition are pivotal in fostering the health autonomy of the golden generation, particularly among primary school-aged children. However, awareness regarding dental care and nutrition significance often lacks among children, especially within the primary school environment. Hence, an effective and innovative educational approach is imperative to instill awareness and healthy habits among young children. Purpose: This study aims to develop and execute a community engagement program focused on cultivating awareness of oral health and optimal nutrition among primary school children at Glagahwero Elementary School, Jember. Implementation: The program will entail employing interactive educational media, including dental and oral health games, and engaging learning materials that are accessible and comprehensible to children. Result: It is envisaged that through this program, there will be an augmentation in knowledge and comprehension among children regarding the importance of oral health and optimal nutrition, as well as the adoption of healthy habits in dental care and dietary choices. Suggestion: Sustainable and collaborative measures need to be undertaken between schools, communities, and local governments to ensure the long-term viability and success of this program.